The Co-Occurrence Of Frailty (Accumulation Of Functional Deficits) And Depressive Symptoms, And Its Effect On Mortality In Older Adults: A Longitudinal Study - Chang HY (Dove Medical Press, 2019)
Hsing-Yi Chang,1,2 Hsin-Ling Fang,1 Te-Tien Ting,3 Jersey Liang,4 Shao-Yuan Chuang,1 Chih-Cheng Hsu,1 Chin-Yin Wu,5 Wen-Harn Pan1,2,6 1Institute of Population Health Sciences, National Health Research Institutes, Maoli, Taiwan; 2Institute of Public Health, National Yang-Ming University, Taipei, Taiwan; 3School of Big Data Management, Soochow University, Taipei, Taiwan; 4Department of Health Management and Policy, School of Public Health, University of Michigan, Ann Arbor, MI, USA; 5Institute of Sociology, Academia Sinica, Taipei, Taiwan; 6Institute of Biomedical Sciences, Academia Sinica, Taipei, TaiwanCorrespondence: Hsing-Yi ChangInstitute of Population Health Sciences, National Health Research Institutes, 35 Keyan Road, A3223, Zhunan Town, Maoli County, ROC 35053, TaiwanTel +886 37 246166Fax +886 37 586261Email hsingyi@nhri.org.twPurpose: The co-occurrence of frailty and depression in late life, the possibility for symptom reversal, their reciprocal relationship, and the effects on mortality have rarely been investigated. We aimed to examine the co-occurrence of frailty and depressive symptoms in late life, the possibility for symptom reversal, their reciprocal relationship, and the effects on mortality using all the information from a longitudinal study.Patients and methods: We used the Taiwan Longitudinal Study of Aging (TLSA) for this study. TLSA was initiated in 1989 and followed periodically. We included participants from 1989 to 2007, who had data on frailty and depressive symptoms. Frailty was assessed by accumulation of functional deficits in 6 dimensions including disease status, sensory dysfunction, balance, functional limitations, health risk behaviors, and life satisfaction. Depressive symptoms were measured with the Center for Epidemiologic Studies Depression Scale (CES-D). A multistate model with interval censoring was used to examine the transition between states of frailty with or without depressive symptoms, and finally to death. A mixed model was used to examine the relationships between frailty and depressive symptoms.Results: The coexistence of frailty and depressive symptoms was associated with higher mortality. Individuals with depressive symptom had a lower probability of reversal to a better state. Previous depression score predicted current frailty, but the coefficient was smaller than that of previous frailty. Previous frailty predicted current depression score, and the coefficient was stronger than that of previous depression.Conclusion: Depressive symptoms increased the mortality and decreased the probability of reversal in the frail older adults.Keywords: TLSA, cumulative functional deficits, depressive symptom, multistate model, mortality